Mapping un/contested knowledge of sex/gender in high performance sport: applying Actor-Network Theory to women`s Olympic Weightlifting - Nelson, M.; Thorpe, H.; Wheaton, B.; Clarke, G. H.; Sims, S. (Qualitative Research in Sport, Exercise and Health, 2026)
Beliefs about women athletes` bodies, physical capacities, and the `best` training methods to attain maximal performance are continually debated inside and outside of sport. But it is unclear how these many disparate, and at times conflicting, knowledges come together to shape women athletes` health and performance. In this paper, we engage Actor-Network Theory (ANT) as a methodological framework for examining the variety of sex and gendered knowledges in sport. To illustrate the functionality of this approach to examine extensive, diverse systems of knowledge, we discuss our operationalisation of ANT as a methodology to examine the sex and gender-focused knowledge networks of Olympic Weightlifting. Drawing from a series of linked qualitative methods, we recount the multitude of contested knowledges about sex, gender, and strength that our mapping made visible, as well as the human and non-human entities that acted to facilitate or hinder their travel throughout the sporting network. Combining actor-network maps with creative non-fiction vignettes, we demonstrate the complex interactions of knowledge that circulated between areas of the network (Olympic Weightlifting gyms, Instagram, academia and the International Weightlifting Federation). We conclude by providing concrete methodological recommendations for future researchers that endeavour to use ANT to study systems of knowledge.